Sexual behavior of protection in adolescents: an approach from the positive psychology (Mayéutica Revista Científica de Humanidades y Artes, 2013)
Nowadays, sexual behavior in teenagers continues being a topic of study for numerous researches, due to the biological, psychological and social repercussions they cause, turning into a problem of public health worldwide and specially in Venezuela. This segment of population is considered to be a vulnerable group due to their own changes at this growing stage, if these changes are not treated adequately teenagers can go through high-risk sexual practices, jeopardizing their own and others’ health. For long, researches focusing on this problem, have addressed a risk approach, intended to prevent pathologies, tossing aside the strengthening of potentials and skills of a person as a mechanism to promote health. Therefore a movement emerges in psychology field: Positive Psychology, which manages to rescue another forgotten opposite side, that is to say, the increase of the potentials, resources, well-being, qualities and positive aspects, and the capacity of overcoming adversities, which up today, they are slightly studied by the risk approach perspective. Studies indicate that protection factors take place to assist teenagers to carry out protection sexual behaviors like sexual resilience, confronting styles, familiar communication, autoefficiency, self esteem and social support. All these qualities and positive aspects seem to be the most convincing reasons to promote sexual healthy behaviors among teenagers and to implement educational programs oriented towards strengthening sexual practices and greater accountability.
Keywords: Protecting factors; sexual behavior protection; adolescence; positive psychology.